An Ontological Model to Apply Gamification as Persuasive Technology in Collaborative Learning Scenarios - Challco, Geiser Chalco; Andrade, Fernando R. H.; Oliveira, Tamires Morete de; Mizoguchi, Riichiro; Isotani, Seiji (Anais do Simpósio Brasileiro de Informática na Educação (SBIE); 2015: Anais do XXVI Simpósio Brasileiro de Informática na Educação, 2015)
The use of Computer-Support Collaborative Learning (CSCL) scripts is an effective approach to support meaningful interactions and better collaborative learning (CL). Unfortunately, in some situations, scripted collaboration decreases the motivation and engagement of students, which makes more difficult to use it over time. To deal with this problem, we propose the use of gamification as Persuasive Technology (PT) to induce the students to follow the intended learning behavior specified by CSCL scripts, with a positive change in the learners’ attitude. Nevertheless, to achieve this goal, it is necessary an exhaustive knowledge on gamification and its impact on CL. Thus, we are developing an ontology to provide a formal systematization of the knowledge on gamification and its proper application in CL scenarios. In this paper, we focus in the formalization of basic concepts related to gamification as a PT in CL scenarios. Furthermore, to demonstrate the applicability of our approach in CL scenarios, we present a case study, where we built and apply a personalized gamification model based on the ontological structures defined in this work.